IMPLEMENTASI KEBIJAKAN TENTANG PERLINDUNGAN ANAK (STUDI KASUS ANAK-ANAK PENGEMIS DI KECAMATAN MANDAU) - Masriani "; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Unity of service prosperity social in Mandau district is not maximal give to protection child order the bigger child in Mandau district. Because lack of supervision, facilities, and affirmation from participants of unity service. Welfare social which authorized in given protection and duty order to the children beggar. Children is eighty yearl old, it is mean still in womb. The protection child is everything activity to ensure and protection child and participants. His night to service, grow, and to participants as optimal with the harkat and dignity. The concept of theory is used according to van meter van horn (2008), state that, there are some variabel which given effect performance implementation the policy of public. This research is used qualitative method with the analyzeddata. As descriptive. Data collection technique was be done in observation, interview, and documentation. The parties muolved in this research as informen. The results of of research showed that implementation of policy about cchild protection (Study Case The children beggar in Mandau district) it is not correct and maximum appropriate because many obstruction was be done in implementation. The obstruction there are facilitaties, actor unity of service prosperity social is not maximal, than lack of communication with local officials, and lack of participant in public rights of the child in the family. keywords: Child, Protection child, Implementation